D-dimer parameters in COVID-19 (Prospective study in 100 patients) (Eurasian Medical Research Periodical, 2023)
A new virus called the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was identified as the cause of a disease outbreak that began in China in 2019. The disease is called coronavirus disease 2019 (COVID-19).